The association between confidence in health system and self-rated health: from the perspective of regional comparison - Wang, Zhaoxi; Zhang, Kairan (Frontiers in Public Health, 2025)
BackgroundUniversal health coverage (UHC) aims to ensure that all people can access quality health services without financial hardship, and thereby improve health outcomes. Confidence in the health system reflects the individuals’ belief that they can obtain or afford care when ill. This study examined the association between health system confidence and self-rated health (SRH) across urban–rural and regional (western, middle, and eastern) areas of China.MethodData were drawn from two waves of the Chinese General Social Survey that included 6,481 participants. Ordered logistic regression was used to assess the association between health system confidence and SRH. Subsample analyses and interaction models were used to explore regional heterogeneity.ResultsBoth self-rated health (SRH) and confidence in obtaining and affording healthcare were higher in urban and eastern regions. Greater confidence in the health system was positively associated with better SRH. Compared to the group without confidence, the group with confidence in getting (β = 0.394, OR = 1.483, p < 0.001) and affording (β = 0.645, OR = 1.906, p < 0.001) healthcare when needed had significant positive associations with better SRH. Confidence in both dimensions showed the strongest effect (β = 0.715, OR = 2.044, p < 0.001). Regarding heterogeneity, affordability-related confidence had particularly strong effects in western regions whereas both dimensions exerted larger effects in rural, compared with urban, areas.ConclusionConfidence in the health system—especially in affordability—is strongly associated with better health outcomes in China. Equity-oriented policies that strengthen both accessibility and affordability, with particular attention to disadvantaged regions and vulnerable populations, are essential for improving health equity.